2017
DOI: 10.3139/146.111557
|View full text |Cite
|
Sign up to set email alerts
|

First principles, thermal stability and thermodynamic assessment of the binary Ni–W system

Abstract: First principles, thermal stability and thermodynamic assessment of the binary Ni-W systemThe Ni-W binary system was assessed using critically evaluated experimental data with assistance from first principles analysis and the CALPHAD method. The solution phases (liquid, fcc-A1 and bcc-A2) were modeled using the substitutional regular solution model. The recently discovered Ni 8 W metastable phase was evaluated as Fe 16 C 2 -like martensite with three sublattices, and shown to be possibly stable according to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The results on Ni-W system have been confirmed since then by several authors, see e.g. [4][5][6][7]. In particular, in Ref.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The results on Ni-W system have been confirmed since then by several authors, see e.g. [4][5][6][7]. In particular, in Ref.…”
supporting
confidence: 58%
“…In particular, in Ref. [6], Isomäki et al, made a complete review (see references therein) and reach the same conclusions.Any discussion is absent from the paper of Meifang Tang et al to rebute the arguments developed in previous literature. The statement 'In their (Isomäki's) assessment, the WNi phase is considered to be metastable' is misleading.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…CALPHAD (CALculation of PHAse Diagram) modelling, which plays a crucial role in understanding complex materials' systems under different conditions, has been leveraged for a better understanding of tungsten steel joining [22]. CALPHAD is a widely used computational approach in materials science to predict phase equilibria in multi-component systems [23]. It utilizes thermodynamic databases containing Gibbs energy data for phases as a function of temperature, pressure, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Ni6W, Ni8W or the richer W-based alloy NiW2(Isomäki et al, 2017), although the existence of this last species was already reported by Poulsen in the 1970s(Poulsen, Rubaek and Langer, 1974). They also indicate the technique(s) used to characterize these species.…”
mentioning
confidence: 82%